Perbedaan Keanekaragaman Lichen di Air Terjun Grojogan Sewu, Air Terjun Jumog, dan Air Terjun Parang Ijo - Maulida, Tiara Wahyu; Muzzazinah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the location with the highest lichen diversity and interpret possible causes based on ecological conditions. Sampling was carried out in June-August 2024 with purposive sampling based on the presence of substrates. The number of plots taken at Grojogan Sewu and Jumog Waterfalls was 4, while the number of plots at Parang Ijo Waterfall was 3 with a plot size of 10 x 10 meters. The types of substrates used were trees, soil, and rocks. The results showed that the lichen found at Grojogan Sewu Waterfall, Jumog Waterfall, and Parang Ijo Waterfall amounted to 14 species from 10 families. The results showed that Parang Ijo Waterfall had the highest level of lichen diversity compared to the other two locations. This finding indicates that environmental conditions in Parang Ijo are relatively more supportive of lichen growth, so that it can be evaluated as an area with better environmental quality. The lichen diversity index at Grojogan Sewu Waterfall is included in the moderate category with H’ 1.12, Jumog Waterfall is included in the moderate category with H’ 1.24, and Parang Ijo Waterfall is included in the moderate category with H’ 1.45.